Review of the main factors controlling the fracture toughness and impact strength properties of natural composites - Al-Maharma, Ahmad Y; Sendur, Polat (Materials research express, 2019)
The main critical factors, which have direct influence on the fracture toughness and imapct strength properties of natural fibers composites, are reviewed in details in this paper. Considering the vast body of literature on the aforementioned subject, there are six main factors controlling these properties: (i) Intrinsic properties of the constituents related to packing arrangements, length, loading and orientation of the fibers; (ii) Type of physical and chemical treatment on natural fibers; (iii) Environmental conditions such as temperature and moisture; (iv) Material properties of reinforcing fiber and hosting resin, which constitute the natural composites; (v) The type of hybridization of natural composites such as self-hybridization based on same natural fiber and hybridization of natural fiber with another natural or synthetic fibers; (vi) Type of nano reinforcements, which is used to improve the fracture toughness of natural composites at nano and micro scale levels. Among the aforementioned factors, it is found out that the most critical factors affecting the fracture toughness and impact strength of natural composites are the type of physical and chemical treatments used to improve interfacial adhesion at fiber-matrix interface and the type of hybridization process.